Spring wheat yield and grain quality response to nitrogen rate. (10th July 2022) - Walsh, Olga S; Marshall, Juliet; Nambi, Eva; Shafian, Sanaz; Jayawardena, Dileepa; Jackson, Chad; Lamichhane, Ritika; Ansah Owusu, Emmanuella; McClintick‐Chess, Jordan
Abstract: Nitrogen (N) is the most limiting nutrient in cereal production, yet its use efficiency remains very low at only 35%. Nutrient use efficiency (NUE) is crucial for increasing crop yield and quality while reducing fertilizer inputs and minimizing environmental damage. Optimum N rates that maximize yield without reducing NUE have been found to vary from location to location. This field study assessed the effect of N rates on the yield and quality of spring wheat ( Triticum aestivum L.) at five locations in southern Idaho in 2015–2017. Nitrogen was applied as urea (46–0–0) immediately after planting at five rates: 0, 84, 168, 252, and 336 kg ha –1 . Nitrogen application improved grain quality (increased protein) even when no increase in yield was noted. Nitrogen use efficiency and N uptake were affected by N rate at only 2 and 4 of 14 site‐years, respectively. These observations highlight the challenging task of pinpointing the appropriate N rates for optimizing wheat yield, grain protein, N uptake and NUE; and the importance of adjusting N rates based on location, year, and prevalent environmental conditions. Core Ideas: Application of all N fertilizer at planting is not efficient for wheat. Nitrogen fertilizer rates for wheat should account for site‐ and year‐specific conditions. When prescribing N rates to wheat, yield potential and responsiveness to N should be considered. Higher N rates resulted in enhanced grain protein content, but low N use efficiency.